The Quality of Life and the Hypoxia Indicator in Survivor of Pediatric Intensive Care Unit in the University of Sumatera Utara Hospital - Malisie, Ririe Fachrina; Tanjung, Ika Citra Dewi (Writing Center IMERI FMUI, 2022)
The technology development for care and management in intensive care units reduces mortality and increases survivors' survival rate and life expectancy. A significant decrease in mortality rate in patients was related to mechanical ventilation. The hypoxia degree and severity of the respiratory distress are the increase of PaO2/FiO2 ratio and decrease of oxygenation index as predictors of oxygenation sufficiency in arterial blood supply to body tissues. The critical parameter of intensive care unit survivors' quality of life is the Pediatric Quality of Life (PedsQL) Inventory score after survival from the pediatric intensive care unit (PICU). During six months of research observation, eight patients died, and 13 patients survived among 68 patients admitted to pediatric intensive care unit who have ventilatory support. The mean PaO2/FiO2 ratio (PFR) in pediatric intensive care survivors who underwent mechanical ventilation was 285, and the mean Oxygenation Index (OI) was 5.07. There was no relationship between PFR and OI with PedsQL score in this study, but we have found a significant correlation between PedsQL and the duration of mechanical ventilation and length of stay in the intensive care unit. The longer mechanical ventilation duration and length of stay in PICU, the lower the pediatric quality of life score.